Crowdsourcing - angażowanie użytkowników bibliotek w tworzenie kolekcji cyfrowych = Crowdsourcing - engaging library users in creation of digital collections - Kowalska, Małgorzata (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
With the development of the concept of Web 2.0, the creation of digital collections engages, apart from traditional cultural institutions (libraries, museums, archives) and their cooperating companies, also Internet users. Over the past 10 years, a large number of different concepts and terms have emerged in attempt to describe this type of participation in culture. One of these terms is crowdsourcing, i.e. handing over one of the organization?s areas to the crowd, an organized Internet community, in the form of an open call. Since the implementation of solutions based on crowdsourcing is quite straightforward, it is initiated more and more often by the libraries. This article presents the idea of crowdsourcing, its types and examples of use.
Keywords: crowdsourcing; Web 2.0; kolekcje cyfrowe; użytkownicy bibliotek; użytkownicy internetu; zaangażowanie; społeczności internetowe; digital collections; library users; Internet users; engagement; online communities